Early signaling in actinorhizal symbioses - Hocher, Valérie (Landes Bioscience, 2011)
Nitrogen-fixing root nodulation, confined to four plant orders, encompasses more than 14,000 Leguminosae species, and approximately 200 actinorhizal species forming symbioses with rhizobia (Rhizobium, Bradyrhizobium, etc.,) and Frankia bacterial species, respectively. While several genetic components of the host-symbiont interaction have been identified in legumes, little is known about the genetic bases of actinorhizal symbiosis. However, we recently demonstrated the existence of common symbiotic signaling pathways in actinorhizals and legumes. Moreover, important data on the identification of flavonoids as plant signaling compounds and the role for auxins during Frankia infection process and nodule organogenesis have been acquired. All together these results lead us to propose a unified model for symbiotic exchange and genetic control of actinorhizal symbiosis.